Integrative taxonomy of the genus Habrophlebia Eaton, 1881 in Morocco (Ephemeroptera, Leptophlebiidae): new species, redescriptions, and morphological-mitochondrial discrepancies - Alami, Majida El; Vuataz, Laurent; Yaagoubi, Sara El; Sartori, Michel (Zootaxa, 2025)
We present a comprehensive overview of the Habrophlebia Eaton, 1881 species inhabiting Morocco. Based on nymphal material, two new species from the Rif Mountain range in northern Morocco are described as Habrophlebia abietis sp. nov. and Habrophlebia linae sp. nov. The descriptions of Habrophlebia vaillantorum Thomas, 1986 and Habrophlebia dakkii El Alami, Vuataz & Sartori, 2023 are emended. Analysis of mtDNA COI affinities and key morphological characters within the investigated populations suggest an important proportion of hybrid populations in the Rif domain, presenting a mix of characters from H. dakkii, H. abietis and H. linae. This finding, rarely documented among mayflies, is discussed.